Exploring and Advancing Healthcare System through Novel Strategies in Pharmacy Field: Life Sciences-Pharmacy - Dr. Ansari Yaasir Ahmed Abdul Razzaq, Guest Editor (International Journal of Life Science and Pharma Research, 2020)
The oral route of drugs administration is the most important method for administering drugs for systemic effects to produce the desired pharmacological actions. Tablets (one of the oral dosage form) are unit solid dosage form containing a drug or drugs with or without additives or excipients and generally prepared by compression method. The objective of the design and manufacture of the compressed tablet is to deliver orally the correct amount of drug or drugs in the desired location and to have its chemical integrity protected to the point. Synthesis and Analytical methods for the drugs are also required to characterize drug substances and drug product composition during all phases of pharmaceutical development. Initial methods must support changes in synthetic routes and dosage form and elucidate the levels of impurities and structures. In later phases, aim change to the development of rapid and robust methods for the stability evaluation and release.